Worldly Punishment of Depravity and Vicious People in the Holy Qur'an - Yahya, Mohammad (Jordan Journal of Islamic Studies, 2023)
This study deals with the subject of the worldly punishment for immorality and immoral people in the Holy Qur’an, as the Qur’an considers immorality among the basics of evils and sins, so the discussion about this scourge came in this study indicating the reality of debauchery and its people, and the penalty for each of its types, and each of its forms. The researcher concluded that debauchery is one of the most serious sins, and that is why Allah has arranged a number of punishments, which vary in strength and weakness, increasing and decreasing in proportion to the extent of penetration into this dangerous scourge.